Effect of the ethanol-fusel oil mixture on combustion stability, efficiency, and engine performance - Mohd Fairusham, Ghazali; S. M., Rosdi; Erdiwansyah, .; Rizalman, Mamat (Elsevier B.V., 2025)
This study explores the effects of ethanol and fusel oil blends on combustion stability, efficiency, and engine performance in spark ignition (SI) engines, driven by the need for alternative fuels to mitigate environmental impacts and reduce fossil fuel dependency. Ethanol and fusel oil, renewable biofuels with distinct combustion properties, were blended with gasoline at 10 %, 20 %, and 30 % by volume and tested at 3000 rpm, 40 % throttle load, and part-load conditions. Ethanol's high-octane number and cooling effect enhance knock resistance, while fusel oil's higher oxygen content and faster combustion kinetics complement its performance. Despite their potential, challenges like combustion stability and engine reliability persist. Blends of ethanol (E10, E20, E30) and fusel oil (F10, F20, F30) were evaluated against gasoline. Results showed increased coefficients of variation in peak pressure (COVpmax), indicating reduced combustion stability: 23.8 % for E10, 30.4 % for E20, 32.9 % for E30, 3.9 % for F10, 9.1 % for F20, and 18 % for F30. This suggests leaner, less stable combustion with higher blend concentrations. Additionally, lower exhaust gas temperatures were observed, reducing NOx emissions but potentially impacting engine reliability. The study underscores the need for further research to identify optimal blend limits and develop adaptive engine strategies, such as air-fuel ratio adjustments or ignition timing modifications, to maintain performance and stability. These findings advance the integration of biofuels in SI engines while addressing environmental and operational challenges.